Human trafficking - Cullen-Dupont, Kathryn (Global issues, 2009)
Human trafficking -- Focus on the United States -- Global perspective -- United States documents -- International documents -- How to research human trafficking -- Facts and figures -- Key players A to Z -- Organizations and agencies -- Annotated bibliography